Literature Review: Microplastic Content in the Digestive Tracts of Fish in Indonesian Waters - Khairunnisak, Khairunnisak; Sahira, Rasyadhifa As; Syafitri, Aini; Chusna, Salsabila Al; Nasir, Muhammad; Rizki, Alia; Firdus, Firdus (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Plastic waste is the biggest problem that is happening in Indonesia. Plastic waste has resistance and the nature of Persiden. Increased production and low recovery rates cause accumulation of plastic flakes in waters called microplastic. Microplastic has the potential to be swallowed by aquatic biota that can cause internal bleeding and blockage of the digestive tract. Hue microplastic will affect humans who consume them. One of the aquatic biota that is often contaminated by microplastic is fish. Research related to microplastic contamination in the digestive tract of fish has often been carried out. This study examines the level of microplastic contamination in the digestive tract of fish in Indonesian waters refers to the available literature. The results showed that there were 5 types of microplastics contaminated in the digestive tract of fish in Indonesia, namely fiber, film/filament, fragments, pellets, rows, foam and granules.